The "social life" of industrial ruins : a case study of Hashima Island - Hong, Insoo (African Studies, 2016)
The inscription of a strange-looking industrial site- coalmine on Hashima- on the World Heritage Site has proved to be the most publicly contested debate of heritage making work between Japan and Korea The debate about this place brings up poignant questions with regard to not only the significance of this heritage, but also the subsequent use of this island. The failure of reconciliation between countries especially, but also of reparation, restitution since the end of the Second World War and the issues of identity and memory have been brought to the fore. This paper seeks to challenge the dominant modes of heritage making and, in so doing, offer an analysis of influences from political, social and economic factors or an improved understanding of the dynamics of capitalistic production expansion. The origin and transformation of tradition is invoked in attempts to explain the pervasiveness and power of historical temporality and continuity. A critical approach to canonisation is employed whereby the choice of heritage resources is done in a more limited and cogent manner. It is argued that currently heritage-making functions as both value distribution and intentional perception for a people in a nation. Above all, the social life of those living in industrial ruins is positioned in the new perspective that as heritage resources they cannot be separated from capitalistic production and world history. Following from this, it is said that the temporality and spatiality of ruins need a political, social and economic debate in which the myths of the nation are forged, transmitted, negotiated and reconstructed constantly. Through employing these ideas, one can relate the thematic approach of heritage selection to commodification, collective memory, capitalism and nationalism in a theoretical and analytical way.